Controllability of non-linear stochastic systems - Mahmudov, NI; Zorlu, S (Taylor & Francis Ltd, 2003)
Complete controllability of a semi-linear stochastic system assuming controllability of the associated linear sytem is studied. It is also shown that a non-linear stochastic system is locally null controllable provided that the corrsponding linearized system is controllable.